Tinjauan Wakalah terhadap Penerapan Sistem Konsinyasi pada Swalayan PT Daya Surya Sejahtera di Ponorogo - Hanafi, Yusron (Institute of Research and Public Service Universitas Jenderal Soedirman, 2024)
Consignment is an agreement that states that the owner of the goods hands over a number of goods to certain parties to sell by providing a commission. This research aims to analyse the application of Islamic law in consignment conducted by PT Daya Surya Sejahtera. This research used inductive analysis method with normative approach of Islamic law. The results showed that the practice of consignment at PT Daya Surya Sejahtera is in line with Islamic law as indicated by the content and ijab qabul contract agreed by both parties.